Factors determining curtailment behaviour of youths: moderating role of government policies - Ahmad, Asad; Garg, Swati; Kirmani, Mohd Danish; Madsen, Dag Øivind (Frontiers in Psychology, 2024)
Introduction Environmental degradation poses a significant threat, making the comprehension of sustainable behaviour imperative for both environmental and business reasons. Embracing sustainable practices and reducing the unnecessary consumption of resources is essential in our current times. One can be sustainable by focusing on either buying sustainable or green products or by using fewer resources, i.e., by adopting curtailment behaviour. The purpose of this study is to determine various factors and their impact on the curtailment behaviour of youths. Methods We used an exploratory and descriptive research design. Responses were generated from 513 young respondents using a structured questionnaire developed based on the extant literature. Results The structural model findings showed that social norms, eco-concern, and religiosity significantly and positively affect curtailment behaviour. However, we observed no significant influence of financial concern or government policy on curtailment behaviour. We also tested the moderation impact of government policy on the relationship between economic concern and curtailment behaviour. The findings suggest that the relationship between eco-concern and curtailment behaviour is stronger for consumers exhibiting higher commitment to government policy. Discussion It is imperative that politicians exercise critical thought and devise strategies to encourage more sustainable consumer behaviour. With the strains that our world is under now and in the future, we need to unite around a common goal: ensuring that our planet is sustainable for coming generations. The study findings are useful for academicians, marketers, and policymakers.